Hubungan Antara Self Esteem dengan Subjective Well Being pada Siswa SMK - Pratiwi, Tites Sri Dewi, Aad Satria Permadi, S.Psi, MA (2016)
Self esteem or self-worth is an assessment or evaluation of individuals who placed themselves in the sense of worth or meaning in individual attitudes towards him. Self esteem can be either a positive attitude and negative attitude, but it shows the extent to which self esteem person considers himself able, meaningful, successful and valuable. Students who have high self esteem have self-contained nature, creative, have personality, stable, and low levels of anxiety. By having these properties will lead to subjective well being on the student. This study aims to determine the relationship between self-esteem with subjective well being, large donations or the role of self-esteem on subjective well being, to determine the extent of self-esteem variable conditions and to determine the extent to which the variable conditions of subjective well being in student of vocational school. The hypothesis of this study is there is a positive relationship between self-esteem with subjective well being in student of vocational school. This means that the higher levels of self-esteem in students of vocational school, the higher subjective well being itself and vice versa. The population in this study are all students of Vocational School Negeri 7 Surakarta and sample in this research is a 79 people of class XI student. The sampling technique is quota sampling. Data collection tools using self esteem scale with the scale of subjective well being. Data is analyzed by using Pearson-product moment correlation. The results of data analysis known that there is a significant positive relationship between self-esteem with subjective well being in student of vocational school. Indicated by (r xy) = 0.727 with a significance of p = 0.000 (p <0:01). So it can be seen that the hypothesis is accepted. Effective contribution given variable to variable self esteem subjective well being of r² = 0.528 or 52.8%. The conclusion from this study is there is a positive relationship between self-esteem with subjective well being on the student of vocational school and the role of self-esteem on subjective well being big enough.